DENTAL SURGEON ETHICS AND DEONTOLOGY (Web of Teachers: Inderscience Research, 2025)
This article tooth surgeons for current happened ethics and deontology to the topics dedicated. Today on the day tooth surgeons needs clinical experience and Medicine of the field development with closely related was new goals puts in the article this of issues in medicine place and importance illuminated.